CDK5-dependent inhibitory phosphorylation of Drp1 during neuronal maturation - Cho, Bongki (Nature Publishing Group, 2014)
Mitochondrial functions are essential for the survival and function of neurons. Recently, it has been demonstrated that mitochondrial functions are highly associated with mitochondrial morphology, which is dynamically changed by the balance between fusion and fission. Mitochondrial morphology is primarily controlled by the activation of dynamin-related proteins including dynamin-related protein 1 (Drp1), which promotes mitochondrial fission. Drp1 activity is regulated by several post-translational modifications, thereby modifying mitochondrial morphology. Here, we found that phosphorylation of Drp1 at serine 616 (S616) is mediated by cyclin-dependent kinase 5 (CDK5) in post-mitotic rat neurons. Perturbation of CDK5 activity modified the level of Drp1(S616) phosphorylation and mitochondrial morphology in neurons. In addition, phosphorylated Drp1(S616) preferentially localized as a cytosolic monomer compared with total Drp1. Furthermore, roscovitine, a chemical inhibitor of CDKs, increased oligomerization and mitochondrial translocation of Drp1, suggesting that CDK5-dependent phosphorylation of Drp1 serves to reduce Drp1's fission-promoting activity. Taken together, we propose that CDK5 has a significant role in the regulation of mitochondrial morphology via inhibitory phosphorylation of Drp1(S616) in post-mitotic neurons.